Mineral supplementation by artificial salt licks is comparatively effective as natural salt licks for Malaysian mammals - Nor Bazilah Razali; Mohammad Saiful Mansor; Farah Ayuni Farinordin; Mohd Izzat-Husna Ahmad Zaini; Siti Hajar Atiqah Razali; Pazil Abdul Patah; Shahril Mod Husin; Mohamed Shah Redza Hussein; Shukor Md Nor (Ecological Processes)
Abstract Background Mineral-rich licks are known to provide mineral supplements to wildlife species, including mammals. Artificial salt licks have been provided as habitat enrichment in protected areas and secondary forests in Peninsular Malaysia since 2012. However, few studies have investigated artificial salt licks, particularly their mineral composition and roles in different habitats. We used 40 camera traps to assess mammal species diversity and assemblages at 20 salt licks (nine natural and 11 artificial licks) in three forest reserves in Peninsular Malaysia. Nine mineral elements from water and soil samples from natural and artificial licks in primary and secondary forests were analysed. Results Twenty-nine mammal species were identified across salt licks, with 16 species being salt lick users, including eight herbivorous, five frugivorous and three carnivorous mammals, most of which moved in groups and solitarily. The mammal species assemblages across both salt lick and habitat types demonstrated a predominantly nested pattern, with herbivorous and frugivorous mammals being the primary users. The artificial salt licks in both habitats showcased the same feeding guilds including species that are resilient to habitat changes. The visitation frequency at both types of licks and habitats suggests that each salt lick user had its own preferences for minerals from salt lick water and soil. Conclusions This study suggests that artificial licks may be as effective as natural licks in providing minerals to many mammal species both in primary and secondary forests. Thus, they could be used to enrich degraded habitats. Enriching degraded habitats is essential for supporting the ecosystem, especially in carbon reduction, biodiversity conservation and connectivity between degraded forests and intact forests.